PROXIMATE FOOD COMPOSITION ON LARVAL DURATION, MORTALITY, SURVIVAL, GROWTH AND FECUNDITY OF PERICALLIA RICINI (FAB.) - SUNDARAMAHALINGAM, A.; CHOCKALINGAM, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
Influence of dietary protein on larval duration, mortality, survival, growth and fecundity of Pericallia ricini was studied by using artificial diet with foul different levels of protein viz. 12, 17, 22 and 26%. The survival, mortality, larval duration and growth of test insect were depended on the amount of protein in the diet. Maximum fecundity was observed (619 eggs) in the optimum level protein (22%) fed groups, while it was minimum (362 eggs) in the low protein diet (17%) fed individuals.